Effect of Coronavirus disease 2019 (COVID-19) on elite Spanish student-athletes` Perception of the dual career - Abenza-Cano, L.; Leiva-Arcas, A.; Vaquero-Cristóbal, R.; García-Roca, J. A.; Meroño, L.; Sánchez-Pato, A. (Frontiers in Psychology, 2020)
The aim of the present research was to assess elite student-athletes` perception of the dual career during the lockdown caused by the coronavirus disease 2019 (COVID-19) pandemic, compared with a group of elite student-athletes who could develop their dual career under normal conditions. A total of 150 elite athletes who were also undergraduate or postgraduate students self-completed the "Perceptions of dual career student-athletes (ESTPORT)" questionnaire. From them, 78 did it during the mandatory lockdown period due to the state of emergency caused by COVID-19 (COVID-19 group) and 72 completed it in the previous year to Rio 2016 Olympic Games (control group). The COVID-19 group was found to spend a significantly higher number of hours per week studying, while no significant differences were observed between groups in any training time variable. Student-athletes of the COVID-19 group showed better perception of whether their sport career could help them cope with their academic career and better general perception of remote learning and the use of tasks and videoconferencing as learning support tools. A lower percentage of athletes of the COVID-19 group than of the control group wished to continue with their sport career once they finished their studies. To conclude, student-athletes of the COVID-19 group show adaptations with regard to the organization of their studies and the importance they give to them and to the services provided by dual-career programs, compared with student-athletes from an ordinary pre-Olympic year. In general, student-athletes` perception of the dual career is very positive.